(Re)Creating Disney: Converging Game World Architecture in Kingdom Hearts - Nguyen, Anh-Thu (Loading)

(untitled) (Canadian Game Studies Association, 2022)
The Kingdom Hearts franchise (2002-2020) is truly a product of convergence culture: in its aesthetics and narrative world, it unites games, films, animations, fairy tales, comics and cartoons. The games’ premise to merge intellectual properties from Disney and Square Enix into one coherent universe strikes as an ambitious effort with contrasting themes, motifs, characters, and worlds sharing a single stage on top of a new cast of characters and an original storyline. An analysis of any franchise is often associated with complex licensing structures, its economic impact, and the great financial endeavour to create multimedia franchises. With a franchise such as Kingdom Hearts however, its franchise relationships to other media can be made apparent through a media-centred analysis, allowing us to understand its franchise character from within. One method to make this approach possible for instance is to look at how the franchise delivers on its cross-collaboration premise by creating game worlds inspired by Disney. Some of these worlds are seemingly exact copies of their original and others deliver a new experience altogether. It is exactly this ambivalence that truly stands out in the franchise, juggling between old and new.